A Multi-Institutional Study Using Simulation to Teach Cardiopulmonary Physical Examination and Diagnosis Skills to Physician Assistant Students. Issue 2 (June 2015) - Multak, Nina; Newell, Karen; Spear, Sherrie; Scalese, Ross J.; Issenberg, S. Barry
Abstract : Purpose: Research demonstrates limitations in the ability of health care trainees/practitioners, including physician assistants (PAs), to identify important cardiopulmonary examination findings and diagnose corresponding conditions. Studies also show that simulation-based training leads to improved performance and that these skills can transfer to real patients. This study evaluated the effectiveness of a newly developed curriculum incorporating simulation with deliberate practice for teaching cardiopulmonary physical examination/bedside diagnosis skills in the PA population. Methods: This multi-institutional study used a pretest/posttest design. Participants, PA students from 4 different programs, received a standardized curriculum including instructor-led activities interspersed among small-group/independent self-study time. Didactic sessions and independent study featured practice with the "Harvey" simulator and use of specially developed computer-based multimedia tutorials. Preintervention: participants completed demographic questionnaires, rated self-confidence, and underwent baseline evaluation of knowledge and cardiopulmonary physical examination skills. Students logged self-study time using various learning resources. Postintervention: students again rated self-confidence and underwent repeat cognitive/performance testing using equivalent written/simulator-based assessments. Results: Physician assistant students (N = 56) demonstrated significant gains in knowledge, cardiac examination technique, recognition of total cardiac findings, identification of key auscultatory findings (extra heart sounds, systolic/diastolic murmurs), and the ability to make correct diagnoses. Learner self-confidence also improved significantly. Conclusions: This study demonstrated the effectiveness of a simulation-based curriculum for teaching essential physical examination/bedside diagnosis skills to PA students. Its results reinforce those of similar/previous research, which suggest that simulation-based training is most effective under certain educational conditions. Future research will include subgroup analyses/correlation of other variables to explore best features/uses of simulation technology for training PAs.